P‐6.1: A study of the fluidity of polyimide alignment agents printed by inkjet printing technology. (24th February 2021) - Che, Xinyuan; Zhao, Yongchao; Song, Yanjun; Hsieh, Chung-Ching; Zhang, Xin
Abstract : The fluidity of polyimide alignment agents has usually been charactrized by their viscosity. Yet, it is not enough for inkjet printing mechines. For samples having the same viscoscity, they may have different molecular weights and molecular weight distributions. And an abnormal molecular weight can induce the blockage of nozzles which will result in suji mura.